Regulatory Mechanisms of Injury and Repair after Hepatic Ischemia/Reperfusion - Alex B. Lentsch (Scientifica)
Hepatic ischemia/reperfusion injury is an important complication of liver surgery and transplantation. The mechanisms of this injury as well as the subsequent reparative and regenerative processes have been the subject of thorough study. In this paper, we discuss the complex and coordinated responses leading to parenchymal damage after liver ischemia/reperfusion as well as the manner in which the liver clears damaged cells and regenerates functional mass.